2020
DOI: 10.2174/1381612825666191119095132
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Associated Neurological Adverse Events: A Case Report and Literature Review

Abstract: Vaccination is an effective strategy to reduce the burden of preventable illness. However, many clinical reports revealed that various vaccinations may associate with neurological disorders, mainly including autoimmune disease, febrile seizure, and vaccine-associated paralytic poliomyelitis (VAPP). Although more and more reports revealed that part of the above post-vaccine neurological disorders is not directly related to vaccination, it may be merely a coincidence. However, these reports may increase the hesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
8
0
2
Order By: Relevance
“…A recent systematic review about the association between different inactivated vaccines (HPV, influenza, tetanus, Bacillus Calmette-Guérin (BCG), polio, or diphtheria) and central demyelinating disorders, however, found no relationship between these vaccines and MS. 33 Similarly, another review of e vaccine-associated neurological adverse events found no direct evidence of increased risk of GBS and anti-NMDA receptor encephalitis after vaccination. 34 Adjuvants are used in such vaccines. They raise concerns about the potential adverse effect they could have, particularly at the injection site and the mediators' responses and inflammatory influx.…”
Section: Inactivated Vaccinementioning
confidence: 99%
“…A recent systematic review about the association between different inactivated vaccines (HPV, influenza, tetanus, Bacillus Calmette-Guérin (BCG), polio, or diphtheria) and central demyelinating disorders, however, found no relationship between these vaccines and MS. 33 Similarly, another review of e vaccine-associated neurological adverse events found no direct evidence of increased risk of GBS and anti-NMDA receptor encephalitis after vaccination. 34 Adjuvants are used in such vaccines. They raise concerns about the potential adverse effect they could have, particularly at the injection site and the mediators' responses and inflammatory influx.…”
Section: Inactivated Vaccinementioning
confidence: 99%
“…66 , 67 The adjuvants used in vaccines, including anti‐SARS‐CoV‐2, might be responsible for potential neurologic adverse effects. 68 Another potential neurological adverse event that may result from vaccination is the immunisation stress‐related response (ISRR), which manifests itself as psychogenic non‐epileptic seizures (PNES). 69 Transverse myelitis, 70 , 71 , 72 GBS, 73 , 74 and Bell's palsy 75 are other potential neurological consequences of the Covid‐19 vaccination reported so far.…”
Section: Neurologic Disordersmentioning
confidence: 99%
“…Tian et al describe a case report where a child presented with acute flaccid paralysis possibly associated with poliovirus vaccination. Vaccine-associated paralytic poliomyelitis (VAPP) and other neurological disorders have been hypothesized to be linked to vaccination; however, no direct evidence suggests that polio vaccination increases the risk of GBS and anti-NMDARe ( Tian et al, 2019 ) [A].…”
Section: Poliovirus Vaccine [Sed-16 257 847–853; Seda-38 320; Seda-39 315–316; Seda-40 391–392; Seda-41 356]mentioning
confidence: 99%